Perlindungan Hukum Zona Ekonomi Eksklusif (ZEE) Terhadap Eksistensi Indonesia Sebagai Negara Maritim - Aditya Taufan Nugraha; Irman Irman (Jurnal Selat, 2014)
Indonesia's sea territory in the Exclusive Economic Zone is an area of the sea that has enormous potential wealth for the prosperity and welfare of the people and the country. Potential of Indonesia's marine wealth that is certainly interesting ZEEI actors are not obliged to take up the richness demanded the government to implement and do protection and law enforcement to keep the existence of Indonesia as a maritime nation in the world. Keywords: ZEE, Maritime Country